ANALISIS STRATEGI PENINGKATAN PENDAPATAN ASLI DAERAH (PAD) DI SEKTOR KESEHATAN DALAM MELAKSANAKAN PEMBANGUNAN KESEHATAN DI KABUPATEN ROKAN HULU - Hasonangan, Pirman (Jurnal Mahasiswa Prodi Manajemen Fakultas Ekonomi, 2016)
This Research aim to to know strategy what better be done/conducte by Public Health Service Sub-Province of Rokan Pate;Upstream so that/ to be Earnings Of Tired Budget Area. Information in relating to done/conducted by strategy is Public Health Service of Rokan Pate;Upstream so that/ to be tired PAD as according to result of research, with data collecting technique pass/through interview and observation. Technique analyse Quantitative Descriptive data and test keapsahan of data with method of Check and of Recheck among/between source of data with source of other data. From result of research got that resistor factor in make-up of area retribution tariff shall be as follows: Lack of the amount of officer of service of transportation medium and retribution in retribution collection, wide of Area reach, Awareness of taxpayer still less, Lack of knowledge about Perda retribution. Of conclusion of done/conducted research result at Public Health Service Sub-Province of Rokan Pate;Upstream with amount of inpormen 8 people and use interview technique can be concluded that publishing Perda about more retribution so that earnings more is mounting, giving goals Earnings of Genuiness Area to each;every Puskesmas so that by the end of goals year determined by Tired Local Government, adding or fund mengoktimalkan which available to operational, giving kewenangan to acceptance bursar in puskesmas to remit to Kasda, doing/conducting agreement to acceptance bursar in puskesmas to remit earnings of tersebut puskesmas in remit to kasda or to Public Health Service in early month;moon, giving fee of punggut bonus or to at acceptance bursar in Public Health Service and of Puskesmas if reached by goals whichHALTED. CROSSING PARAGRAPH LIMITATION